Integrating Traditional Fish-Processing Ethnoscience and Digital Interactive Boards in Deep Learning to Enhance Coastal Elementary Students’ Scientific Literacy - Trisniati; Aynin Masfufah; Ratna Ekawati; Riska Pristiani; Slamet Arifin (Universitas Negeri Padang, 2026)
The Programme for International Student Assessment (PISA) 2022 reported that Indonesia's science literacy score reached only 383, placing the country 67th out of 81 participating nations, with students in coastal areas facing even greater challenges due to limited access to contextual learning resources. Science instruction in coastal elementary schools remains predominantly theoretical and disconnected from students' daily experiences with marine resources, while local wisdom in traditional fish processing, rich in scientific principles such as osmosis, evaporation, and fermentation, has yet to be systematically integrated into the curriculum. This literature study aims to analyze the integration of traditional fish processing ethnoscience and digital interactive boards within the deep learning framework to enhance science literacy among coastal elementary school students. The study employed a qualitative literature review approach, with data collected from ten relevant articles published between 2015 and 2026, sourced from Google Scholar, ERIC, and ScienceDirect, and analyzed using content analysis techniques. The findings reveal three key contributions: first, traditional fish processing practices contain scientific concepts that can be reconstructed into contextual learning materials; second, digital interactive boards effectively facilitate visualization, simulation, and collaboration essential for deep learning; and third, the synergy between ethnoscience and digital technology within the deep learning framework offers a holistic pedagogical model. The study's primary contribution is the formulation of a conceptual framework demonstrating that the simultaneous integration of ethnoscience, digital interactive boards, and deep learning principles, mindful, meaningful, and joyful learning, can serve as an evidence-based pedagogical strategy to bridge the gap between formal science education and the socio-cultural realities of coastal communities, thereby offering a practical reference for developing contextual science instruction in similar settings